2010
DOI: 10.1016/s1607-551x(10)70060-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Physical Therapy Intervention on Ventilator Weaning and Functional Status

Abstract: Our study aimed to understand the characteristics of ventilator dependence in patients at a respiratory care center and the potential effects of physical therapy on ventilator weaning and patients' functional status. Prospective data collection consisted of the following: (1) demographic data, including name, gender, age, diagnosis, the Acute Physiology and Chronic Health Evaluation as a severity of the disease, modified Glasgow Coma Scale, mobility at the time of admission, and days of hospitalization; (2) Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 8 publications
1
25
0
3
Order By: Relevance
“…The results of Yang et al ,2010 [24] matches with the present study which sowed a non significant differences between both groups as regards the rate of successful weaning that was lower in that reported by Yang et al, as their study did not include threshold inspiratory training. They used traditional abdominal training and inspiratory muscle weight training combined with mobilization training.…”
Section: Comparison Between Group a And Group B Post Trainingsupporting
confidence: 87%
“…The results of Yang et al ,2010 [24] matches with the present study which sowed a non significant differences between both groups as regards the rate of successful weaning that was lower in that reported by Yang et al, as their study did not include threshold inspiratory training. They used traditional abdominal training and inspiratory muscle weight training combined with mobilization training.…”
Section: Comparison Between Group a And Group B Post Trainingsupporting
confidence: 87%
“…Nevertheless, it was confirmed that appropriate rehabilitation during hospital stay increases the BI approximately twofold and the weaning success by about 50% [21], while early mobilization is a positive independent factor contributing to being discharged home [23]. Ceriana et al [24] also demonstrated that, after rehabilitation during respiratory ICU stay, the mean Dependence Nursing Scale score improved, decreasing from 23 to 12 points.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos conduzidos em pacientes crĂ­ticos submetidos a VMI, admitidos em UTIs clĂ­nicas ou cirĂșrgicas, ou ainda em unidades respiratĂłrias nĂŁo mostraram diferenças no tempo de VMI (30)(31)(32) , tempo de internação na UTI (30,31,33) , frequĂȘncia de pneumonia associada Ă  ventilação mecĂąnica (31) e mortalidade (30)(31)(32)(33) entre pacientes que recebiam assistĂȘncia fisioterapĂȘutica e pacientes do grupo controle, nĂŁo assistidos pela fisioterapia.…”
Section: Impacto Da AssistĂȘncia FisioterapĂȘutica Ao Paciente CrĂ­tico unclassified
“…A assistĂȘncia fisioterapĂȘutica oferecida nestes estudos consistia de uma (32) , duas (30,31) , ou seis (33) sessĂ”es diĂĄrias de fisioterapia respiratĂłria que compreendia posicionamento, higiene brĂŽnquica e aspiração (30,31) ; ou treinamento de respiração abdominal e da musculatura respiratĂłria, exercĂ­cios ativos e passivos de membros superiores e inferiores, e treino de mobilidade progressiva (32) ; ou ainda, exercĂ­cios para os mĂșsculos respiratĂłrios, tĂ©cnicas de re-expansĂŁo pulmonar e remoção de secreçÔes brĂŽnquicas, quando apropriados (33) . AlĂ©m da grande heterogeneidade de condiçÔes clĂ­nicas, padronização das tĂ©cnicas realizadas e nĂșmero amostral comprometido, estes estudos nĂŁo focaram na duração do turno diĂĄrio de assistĂȘncia fisioterapĂȘutica na UTI.…”
Section: Impacto Da AssistĂȘncia FisioterapĂȘutica Ao Paciente CrĂ­tico unclassified